The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5888/pcd11.130259
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Health Literacy on Education Retention of Stroke Patients

Abstract: Introduction Inadequate health literacy is a pervasive problem with major implications for reduced health status and health disparities. Despite the role of focused education in both primary and secondary prevention of stroke, the effect of health literacy on stroke education retention has not been reported. We examined the relationship of health literacy to the retention of knowledge after recommended stroke education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…(Danzl, et al, 2013; S. R. Magasi, et al, 2008) A recent study by Sanders et al (2014),(Sanders et al, 2014) showed that even after receiving recommended stroke education, only 12% of the subjects could identify all 5 warning signs for stroke, 43% could name all of their personal risk factors, and fewer than half could identify the type of stroke they had suffered. These findings indicate the need for follow-up education beyond that which is provided during the acute rehabilitation stay.…”
Section: Discussionmentioning
confidence: 99%
“…(Danzl, et al, 2013; S. R. Magasi, et al, 2008) A recent study by Sanders et al (2014),(Sanders et al, 2014) showed that even after receiving recommended stroke education, only 12% of the subjects could identify all 5 warning signs for stroke, 43% could name all of their personal risk factors, and fewer than half could identify the type of stroke they had suffered. These findings indicate the need for follow-up education beyond that which is provided during the acute rehabilitation stay.…”
Section: Discussionmentioning
confidence: 99%
“…61 Limited health literacy contributes to poor diseaserelated knowledge, low perceived disease self-management skills, poor quality of life indicators, and detrimental health outcomes, including premature mortality. 7,25,62 The impact of low health literacy on self-management program enrollment and retention has yet to be fully explored, especially among patients living with chronic lower respiratory conditions. 62 However, the use of health literacy strategies to increase patient access to understandable and actionable self-management information has been shown to increase disease-specific knowledge 62 and activate patient health care decision-making.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…[16][17][18] However, current literature provides conflicting evidence regarding the long-term benefits of participating in chronic disease self-management programs. 4,[19][20][21][22] Patients with advanced stages of chronic disease (eg, type 2 diabetes, chronic lower respiratory conditions, cancer) generally experience severe symptoms and high rates of premature mortality, 10,23 which partially contributes to small sample sizes (eg, [20][21][22][23][24][25][26][27][28][29][30] 19,24,25 and high attrition in self-management programs. 23,26,27 However, researchers argue that understanding reasons for patients choosing to enroll/not enroll and participate in self-management can be determined by exploring patient attitudes and beliefs on factors that affect recruitment and retention.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses have been recognized as crucial members in the multidisciplinary team and one role of the nurse is to enable stroke survivors and caregivers to cope and adjust with changes through a discharge planning process (Portillo et al 2009, Kerr 2012. This is particularly important for first-time stroke survivors and caregivers considering their low levels of health literacy, unfamiliarity with sources of care and rehabilitation programmes, knowledge and skill deficits in managing daily care activities, preventing secondary stroke and stroke associated adverse events (Laver et al 2010, Ostwald et al 2013, Sanders et al 2014).…”
Section: Introductionmentioning
confidence: 99%